2013
DOI: 10.1016/j.hlc.2012.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Dabigatran for Anticoagulation in Atrial Fibrillation – Early Clinical Experience in a Hospital Population and Comparison to Trial Data

Abstract: In this population our study demonstrates a discontinuation rate of 10% due to side effects of dabigatran, similar to the rate reported in RE-LY. The majority of patients are satisfied with their treatment and preferred dabigatran to warfarin, mainly due to the reduced requirement for blood testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 16 publications
1
8
0
5
Order By: Relevance
“…Unfortunately, information from large randomised controlled studies (4,18) cannot provide a reliable indication of levels of persistence that might be anticipated in real world practice. Some studies, largely from pharmacy or health system administrative data and all limited to a single NOAC have attempted to estimate persistence and in some studies to determine whether that NOAC drug showed improved persistence compared with VKA (19)(20)(21)(22)(23)(24). To address this important question of OAC persistence in real-world practice following the approval of NOACs, we conducted a cohort study in the UK general practice of patients with a first diagnosis of AF, comparing VKA with NOAC persistence, i. e. the probability of continuing on OAC treatment at one year after the initiation of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, information from large randomised controlled studies (4,18) cannot provide a reliable indication of levels of persistence that might be anticipated in real world practice. Some studies, largely from pharmacy or health system administrative data and all limited to a single NOAC have attempted to estimate persistence and in some studies to determine whether that NOAC drug showed improved persistence compared with VKA (19)(20)(21)(22)(23)(24). To address this important question of OAC persistence in real-world practice following the approval of NOACs, we conducted a cohort study in the UK general practice of patients with a first diagnosis of AF, comparing VKA with NOAC persistence, i. e. the probability of continuing on OAC treatment at one year after the initiation of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Even more alarmingly, the rate of major gastrointestinal bleeding was 4.11%/year in our cohort, substantially higher than that of both the Asian (0.96%/year to 1.15%/year) and non-Asian population (1.14%/year to 1.69%/year) in the RE-LY study [21]. While some studies in the real world setting documented very few bleeding events, ranging from 3.3% to 5.2%,[16], [18], [22] Michel and colleagues revealed that 29% of patients receiving dabigatran had experienced bleeding events, predominantly minor ones [23]. In particular, Ho and colleagues reported the total bleeding and intracranial hemorrhagic risks of 22.95% and 1.64%, respectively, which were even higher than that in our cohort [17].…”
Section: Discussionmentioning
confidence: 99%
“…33 In a prospective observational study from New Zealand 24% of the 70 patients discontinued dabigatran; 4 due to gastrointestinal side effects, 3 due to bleeding, and 19 reported difficulty with the twice daily dosing regimen, whereas 13 of 70 reported missed doses. 34 Few studies have been recently reported which specifically looked into adherence with NOACs. A retrospective preimplementation-postimplementation study conducted at a Veterans Affairs hospital which utilized medication possession ratio (MPR) with acceptable adherence, defined as an MPR of !…”
Section: Current Available Real-world Data On Dabigatranmentioning
confidence: 99%